(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s ((3eMeO Hf CHj WGdH GdHOQj s)
(3ChdgG (B:s
(3hVGM dbH ZdH Ydjg dLeGdg hHgGFg, hCSeg YHOGdQMef Hf ESeGYjd Hf YHO cdGd Ke jNJda aj JMbjb fSHg ajbhd bhe(B: (3Efg ef ChdGO bQjT GdPjf bOehG Gdjef s
(3BNQgG (B:s
(3Mqj GdefGRd EP dG fHJZj HOdkG HGdOGQ OGQG hdG GdLjQGf LjQGfG hPcQ GHf Gdecj Cfg deYHO, gPG BNQ GdLRA GdSGOS, jJdhg aj GdSGHY fSH LQjQ hCNHGQg s
(3ef fSNI JGSYIs
(3hQO CjVkG JMJ Qbe (B2176s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B46 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B129s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs